The Organization of Economy Within a Communist Society: On Marx’s Theory of the Three Moments and Some Contemporary Perspectives - Sotomayor Trelles, José Enrique (2024)
This paper has two aims. First, it attempts to sketch what one may call the “theory of the three moments”–a theory concerning the transition to communism–in Karl Marx’s works: seizure of power through democratic means, progressive destruction of the mechanisms of class domination, and organization of a new society of free and associated producers. The second aim of this paper returns to the horizon of possibilities regarding the organization of economy in a society where the remains of the capitalist mode of production have been destroyed. Concerning this point, the relevant passages of Marx’s work are neither abundant nor detailed. However, some of them focus on the perspectives of the cooperative organization of the Paris Commune. Going beyond Marx, the paper also reviews some contemporary approaches that take up the path towards an emancipated future.